ANALISIS FOTO PRODUK SEPATU ZX 8000 LEGO® DENGAN PENDEKATAN SEMIOTIKA ROLAND BARTHES - Septian, Nandang (Universitas Mercu Buana, 2023)
A prominent global shoe brand, such as Adidas, is intricately linked to its identity as a product and a fashion symbol. The brand's commitment to innovation and development is evident through various collaborations, a notable example being the partnership with Lego. The focus of this research is the ZX 8000 Lego® shoes, a product made from the fusion of Adidas and Lego. Analyzing the product photo of these shoes serves as the basis for exploring symbols and their meanings. Product photos, as a powerful tool, contain information that captivates consumers and influences purchasing decisions. This qualitative research, employing a descriptive analysis method with the Roland Barthes Semiotics approach, delves into denotation (signifiers) and connotation (signified) meanings within the elements of the product photo. The identified meanings lay the groundwork for unraveling the myth or ideology embedded in the product photos. The study reveals denotations like dominant shoe pairs, vibrant colors, contrasting materials, dual logos, scattered Lego blocks, a white background, and trademark presence. Connotations, on the other hand, revolve around roles, harmonization of meaning, strategic displays, simplicity as a value, and trademarks as assets and symbols of approval. These meanings collectively aim at attracting new consumers, suggesting an underlying ideology favoring capitalism. Despite this, the collaboration proves mutually beneficial, portraying a harmonious coexistence that benefits both brands.